Neuroprediction and A.I. in Forensic Psychiatry and Criminal Justice: A Neurolaw Perspective - Tortora, Leda; Meynen, Gerben; Bijlsma, Johannes; Tronci, Enrico; Ferracuti, Stefano (Frontiers in Psychology, 2020)
Advances in the use of neuroimaging in combination with A.I., and specifically the use of machine learning techniques, have led to the development of brain-reading technologies which, in the nearby future, could have many applications, such as lie detection, neuromarketing, brain-computer interfaces. They could, in principle, also be used in forensic psychiatry. The application of these methods to forensic psychiatry could, for instance, be helpful to increase the accuracy of risk assessment and to identify possible interventions. This technique could be referred to as 'A.I. neuroprediction’, and involves identifying potential neurocognitive markers for prediction of recidivism. However, the future implications of this technique and the role of neuroscience and A.I. in violence risk assessment remain to be established. In this paper, we review and analyze the literature concerning the use of brain-reading A.I. for neuroprediction of violence and rearrest to identify possibilities and challenges regarding the future use of these techniques in the fields of forensic psychiatry and criminal justice, considering legal implications and ethical issues raised.The analysis suggests that additional research is required on A.I. neuroprediction techniques, and there is still a great need to understand how they can be implemented in risk assessment in the field of forensic psychiatry. Besides the alluring potential of A.I. neuroprediction, we argue that its use in criminal justice and forensic psychiatry should be subjected to thorough harms/benefits analyses not only when these technologies will be fully available, but also while they are being researched and developed.